PEMBENTUKAN PENGADILAN AGRARIA DALAM PENYELESAIAN SENGKETA PERTANAHAN DI INDONESIA - Cindy Nabila Saraswati (Fakultas Syariah dan Hukum Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2021)
The background of this research is due to the high number of land disputes in Indonesia that have not been resolved by the District Courts and State Administrative Courts. Land dispute cases that have not been resolved and are still in the process of being resolved result in the absence of legal certainty and expediency to the disputing parties over the status of the disputed land. This journal writing focuses on the role of the District Courts and State Administrative Courts in resolving land disputes in Indonesia and the urgency of establishing a special agrarian court to realize legal certainty and expediency. The research method used in writing this journal is juridical normative through a conceptual approach and a statutory approach. The results of this research is that the District Courts and State Administrative Courts have not been able to resolve existing land disputes optimally, this can be seen from the high percentage of land disputes that have not yet been resolved and are still in the process of being resolved and it is necessary to establish an Agrarian Court as a Special Court that will resolve land disputes in Indonesia, a judgement issued by a Agrarian Court will provide more legal certainty and expediency to the disputing parties.